Modulation‐Based Atom‐Mirror Entanglement and Mechanical Squeezing in an Unresolved‐Sideband Optomechanical System. Issue 7 (16th April 2019) - Bai, Cheng‐Hua; Wang, Dong‐Yang; Zhang, Shou; Liu, Shutian; Wang, Hong‐Fu
Abstract: A hybrid optomechanical system which is composed of an atomic ensemble and a standard optomechanical cavity driven by a periodically modulated external laser field is investigated. Based on the simple periodic modulation forms of the driving amplitude and effective optomechanical coupling, respectively, the atom‐mirror entanglement is discussed in detail. It is found that the maximum of the entanglement in the unresolved‐sideband regime can be further enhanced compared with the non‐modulation regime. On the other hand, we find that the introduction of the atomic ensemble permits the mechanical squeezing induced by the periodic amplitude modulation can be successfully generated even in the unresolved‐sideband regime. Due to the self‐cooling mechanism constructed by the atomic ensemble, the mechanical squeezing scheme no longer requires the extra precooling technologies. Abstract : The periodic modulation technologies of the driving amplitude and effective optomechanical coupling are applied to a hybrid optomechanical system which is composed of an atomic ensemble and a standard optomechanical cavity. The modulation not only further enhances the maximum of the atom‐mirror entanglement in an unresolved‐sideband cavity, but also successfully generates the mechanical squeezing in the unresolved‐sideband regime.